Dynamic response and hydrodynamic coefficients of a cylinder oscillating in crossflow with an upstream wake interference. (1st August 2020) - Lin, Ke; Fan, Dixia; Wang, Jiasong
Abstract: Flow-induced vibrations (FIV) of the cylinder with an upstream wake interference is rather different and more complex comparing with vortex-induced vibrations (VIV) of an isolated cylinder in the uniform flow, due to the wake interference mechanism involved. In this study, the forced vibration experiment is carried out on a rigid cylinder placed in tandem downstream of a stationary cylinder. The hydrodynamic coefficients of the forced vibrating cylinder, involving the steady drag coefficient C d, the excitation coefficient C l v and the added mass coefficient C m y, are obtained for the gap ratio G / d = 2–8 (where G is the streamwise distance between the centers of two cylinders and d is the cylinder diameter). Compared with an isolated cylinder, the mean drag coefficient is dramatically reduced, and a much broader positive C l v that extends to higher amplitude and lower reduced frequency is observed, the negative added mass coefficient presents for lower reduced frequency, for the cylinder with an upstream wake interference. A significant change in the distribution of hydrodynamic coefficients is found during the flow interference mode converting from the proximity interference into the full wake interference. By means of discrete vortex method (DVM) simulations, the free dynamic response of an elastically mounted cylinder placed in the wake of a stationary cylinder is numerically simulated. Comparison between the free and forced vibration of the downstream cylinder shows a good agreement between the superposed free-vibration response plot and the contour line of zero C l v . This result confirms the correlation between free and forced vibration for the cylinder FIV response with an upstream wake interference, and further suggests that the forced vibration can be one approach to predicting the dynamic response and mapping the hydrodynamic properties of the FIV of multiple interfering cylinders. Highlights: The forced vibration experiment is carried out on a rigid cylinder placed in tandem downstream of a stationary cylinder. The correlation between free and forced vibration is confirmed for the cylinder FIV with an upstream wake interference. This study suggests that the forced vibration can be used to map the hydrodynamic properties of the multiple cylinders FIV. The hydrodynamic properties are characterized for the cylinder FIV with an upstream wake interference.